Detection of Carbon Monoxide’s 4.6 Micron Fundamental Band Structure in WASP-39b’s Atmosphere with JWST NIRSpec G395H - David Grant; Joshua D. Lothringer; Hannah R. Wakeford; Munazza K. Alam; Lili Alderson; Jacob L. Bean; Björn Benneke; Jean-Michel Désert; Tansu Daylan; Laura Flagg; Renyu Hu; Julie Inglis; et al. (The Astrophysical Journal Letters, 2023)
Carbon monoxide (CO) is predicted to be the dominant carbon-bearing molecule in giant planet atmospheres and, along with water, is important for discerning the oxygen and therefore carbon-to-oxygen ratio of these planets. The fundamental absorption mode of CO has a broad, double-branched structure composed of many individual absorption lines from 4.3 to 5.1 μ m, which can now be spectroscopically measured with JWST. Here we present a technique for detecting the rotational sub-band structure of CO at medium resolution with the NIRSpec G395H instrument. We use a single transit observation of the hot Jupiter WASP-39b from the JWST Transiting Exoplanet Community Early Release Science (JTEC ERS) program at the native resolution of the instrument ( R ∼ 2700) to resolve the CO absorption structure. We robustly detect absorption by CO, with an increase in transit depth of 264 ± 68 ppm, in agreement with the predicted CO contribution from the best-fit model at low resolution. This detection confirms our theoretical expectations that CO is the dominant carbon-bearing molecule in WASP-39b’s atmosphere and further supports the conclusions of low C/O and supersolar metallicities presented in the JTEC ERS papers for WASP-39b.